Defective N/S‐Codoped 3D Cheese‐Like Porous Carbon Nanomaterial toward Efficient Oxygen Reduction and Zn–Air Batteries. Issue 21 (18th April 2018) - Zhu, Jiawei; Li, Wenqiang; Li, Shuaihu; Zhang, Jian; Zhou, Huang; Zhang, Chengtian; Zhang, Jianan; Mu, Shichun
Abstract: Developing a facile and cost‐efficient method to synthesize carbon‐based nanomaterials possessing excellent structural and functional properties has become one of the most attractive topics in energy conversion and storage fields. In this study, density functional theory calculation results reveal the origin of high oxygen reduction reaction (ORR) activity predominantly derived from the synergistic effect of intrinsic defects and heteroatom dopants (e.g., N, S) that modulate the bandgap and charge density distribution of carbon matrix. Under the guidance of the first‐principle prediction, by using ultralight biomass waste as precursor of C, N, and S elements, a defect‐rich and N/S dual‐doped cheese‐like porous carbon nanomaterial is successfully designed and constructed. Herein, the intrinsic defects are artfully generated in terms of alkaline and ammonia activation. The electrochemical measurements display that such a material owns a comparable ORR activity ( E 1/2  = 0.835 V) to the commercial Pt/C catalyst, along with splendid durability and methanol tolerance in alkali media. Furthermore, as cathode catalyst, it displays a high Zn–air battery performance. The excellent ORR activity of the catalyst can be attributed to its unique 3D porous architecture, abundant intrinsic defects, and high‐content active heteroatom dopants in the carbon matrix. Abstract : N/S‐codoped cheese‐like porous carbon nanomaterials with abundant intrinsic defects show a comparable oxygen reduction reaction activity and Zn–air battery performance to the commercial Pt/C catalyst, resulting from the synergistic effect of intrinsic defects and heteroatom dopants that modulate the bandgap and charge density distribution of carbon matrix.